Convergent Validity of the Dutch Central Sensitization Inventory: Associations with Psychophysical Pain Measures, Quality of Life, Disability, and Pain Cognitions in Patients with Chronic Spinal Pain. Issue 6 (2nd February 2018) - Kregel, Jeroen; Schumacher, Charline; Dolphens, Mieke; Malfliet, Anneleen; Goubert, Dorien; Lenoir, Dorine; Cagnie, Barbara; Meeus, Mira; Coppieters, Iris
Abstract: Objective: Symptoms of central sensitization (CS) have been described in patients with chronic spinal pain (CSP). Although a gold standard to diagnose CS is lacking, psychophysical pain measures are often used. The Central Sensitization Inventory (CSI) is proposed as an alternative method and indirect tool for the evaluation of CS symptomatology. The aim of the current study was to evaluate the convergent validity of the CSI by investigating the association with psychophysical pain measures and self‐reported measures of current pain intensity, quality of life, disability, and catastrophizing in CSP patients. Methods: One hundred sixteen patients with nonspecific CSP were included in the present study. Patients completed the CSI, were subjected to pressure pain thresholds (PPTs) and a conditioned pain modulation (CPM) paradigm, and completed questionnaires for current pain intensity, quality of life, pain disability, and pain catastrophizing. Results: Higher CSI scores were weakly correlated with lower PPTs (−0.276 ≤ r ≤ −0.237; all P ≤ 0.01) and not with CPM efficacy ( r = 0.017; P = 0.858). Higher CSI scores were moderately correlated with higher current pain intensity ( r = 0.320; P < 0.001), strongly correlated with lower physical ( r = −0.617; P < 0.001) and emotional ( r = −0.635; P < 0.001) quality of life, and moderately correlated with higher pain disability ( r = 0.472; P < 0.001) and higher pain catastrophizing ( r = 0.464; P < 0.001). Conclusion: The CSI was weakly associated with PPTs and not with CPM efficacy in CSP patients. Moderate to strong associations were found with current pain intensity, quality of life, disability, and catastrophizing. The current results illustrate that the CSI does not reflect a direct measure of CS, yet is a representation of general distress, possible originating from CS symptoms.